"Doing Something": African American Male Adolescent/Parent Experiences and Perceptions About Bullying. Issue 4 (October 2022) - Cronin, Travis W.; Lateef, Husain; Jayasundara, Dheeshana S.
This was an exploratory phenomenological study regarding experiences and perceptions about bullying among African American male adolescents (AAMAs) and their parents. The sample for this study included 16 AAMAs and 16 parents (one AAMA and one matched parent per family; N = 32). This study was designed to understand what AAMAs and their parents gleaned from their experiences with bullying. The findings were organized into three themes: interpersonal and structural barriers that hindered responses to bullying, intentional systemic approaches to prevent and respond to bullying, and taking direct action when bullying occurred.